Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I know that the derivative of the inverse function of $f(x)$ is $g'(y) = \frac{1}{f'(x)}$ But how to derive the formula for the second derivative of g(y) knowing that $\left[\frac{1}{f(x)}\right]' = -\frac{f'(x)}{(f(x))^2}$ ?

I just started studying this chapter, so please try to be as simple as possible ;-) Thank you.

share|improve this question
add comment

2 Answers 2

up vote 2 down vote accepted

It is $$g(f(x)) = x \Longrightarrow g'(f(x))\cdot f'(x) = 1 \Longrightarrow g''(f(x))\cdot f'(x)^2+g'(f(x))\cdot f''(x) = 0 \Longrightarrow g''(y) = -\frac{f''(x)}{f'(x)^3}$$

share|improve this answer
    
thank you! it was really that simple! Just a single question: if f(x) = g(x), can I also precisely say that f'(x) = g'(x)? Because you used this property at the second implication... –  Umar Jamil Dec 2 '12 at 16:30
    
Yes .. if you have two identical functions they have the same derivation. I used this fact twice (for the first implication and for the second implication also) –  user127.0.0.1 Dec 2 '12 at 18:49
add comment

Note that $y = f(x)$ and $x = g(y)$ in the formula $g'(y) = \frac{1}{f'(x)}$. Hence you can now write $$ g'(y) = \frac{1}{f'(g(y))} \, . $$ Now use the chain rule and the known formula for $g'(y)$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.